The Application of Fishbone Diagram Analisis to Improve School Quality - Slameto, Slameto (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2016)
The research problems are: 1) What steps are to take in a program development aimed at improving the quality of school using a fishbone analysis? 2) Is the program model using fishbone analysis effective and efficient in meeting the school’s needs to improve its quality? This is research and developmental which comprises 3 phases, namely Preliminary Study, Model Development, and Evaluation/Model Testing. The qualitative data come from the input of management experts and the result of interviews/FGD with stakeholders. The quantitative data are obtained from the assessment of management experts on the product draft, the observation sheets for the field study on the standards of education, and the try out. Data analisis on the validation result uses a descriptive analysis technique. Data from the questionnaire are analyzed by descriptive statistical technique. The results are: 1) the developmental steps in the school quality improvement program by way of fish bone analysis have gone through 6 phases, 2) the research product using fish bone diagram has proved to be simple, applicable, important, controllable, as well as adaptable. Furthermore, it is communicable, so that it has been effective and efficient in meeting the school’s needs for making its educational quality improved.